Safety, Tolerability, Pharmacokinetic and Pharmacodynamic Evaluations Following Single Oral Doses of GSK2330672 in Healthy Japanese Volunteers. Issue 1 (5th June 2018) - Ino, Hiroko; Endo, Akira; Wakamatsu, Akira; Ogura, Hirofumi; Numachi, Yotaro; Kendrick, Stuart
Abstract: GSK2330672 is an inhibitor of the ileal bile acid transporter, designed to have minimal systemic exposure, and is under development as a potential therapeutic for pruritus associated with primary biliary cholangitis and other cholestatic liver diseases. A phase 1, double‐blind, placebo‐controlled, 4‐period crossover study was conducted to evaluate the safety, tolerability, and pharmacokinetic/pharmacodynamic characteristics of GSK2330672 in healthy Japanese participants. Sixteen healthy male participants received single oral doses of GSK2330672 (10‐180 mg) or placebo in each period. No serious adverse events and no adverse events leading to study discontinuation or withdrawal were reported. Drug‐related adverse events reported included gastrointestinal symptoms (mostly diarrhea) and positive fecal occult blood tests, and were all mild and resolved without any interventions. GSK2330672 was undetectable in the majority of participants' plasma. Pharmacodynamic observations included a tendency for total serum bile acids to reduce and for serum 7α‐hydroxy‐4‐cholesten‐3‐one, a key intermediate of bile acid synthesis, to increase with increasing doses of GSK2330672. In the context of recently published indications of potential efficacy for cholestatic pruritus in non‐Japanese populations, these data support further evaluations of GSK2330672 in Japanese patients.